Apples-or-oranges? The current landscape of nontargeted metabolomics for food analysis - Odenkirk, Melanie T.; Ahmed, Selena; De la Parra, John; Chien, Chi-Ming; Brinkley, Sarah; Shafizadeh, Tracy; Watkins, Steve; Prenni, Jessica E. (2024)
Despite a remarkable advancement in analytical and informatic resources, the characterization of food composition has remained stagnant, focusing on at most 100 compounds with recognized nutritional value. In this study, we employ nontargeted metabolomics to examine nine identical food types, assessing the diverse small molecule landscape across three reputable, independent laboratories. Notably, each lab employed distinct sample preparation, data acquisition, and data processing methods. Our ﬁndings shed light on the present state of inter- and intra-laboratory translatability in nontargeted metabolomics, offering insights crucial for the evolution of next-generation food composition analysis using the Periodic Table of Food Initiative (PTFI) methods.